Sistematik Review: Kepatuhan Hukum dan Keberlanjutan Perikanan: Studi Biologi dan Hukum tentang Praktik Penangkapan Ikan di Kawasan Konservasi - Suar Bhakti Ibrahim, Arisman; Ridwan; Filtar, Muhammad (Universitas Muslim Buton, 2024)
Conservation areas play a crucial role in maintaining fisheries sustainability and protecting marine ecosystems. However, adherence to legal regulations often poses significant challenges that impact the effectiveness of management in these areas. This study aims to evaluate the relationship between legal compliance and fisheries sustainability in conservation areas using a systematic review approach. The methodology includes searching literature from major academic databases, selecting studies based on inclusion and exclusion criteria, and thematic synthesis of the findings. The analysis focuses on the impact of legal compliance on ecosystem health, challenges in law enforcement, and the biological impacts of fishing practices. Findings indicate that conservation areas with high legal compliance generally experience improvements in fish biomass and biodiversity. Conversely, weak law enforcement is often confronted with issues such as resource shortages and corruption, which reduce management effectiveness and lead to habitat degradation and declines in target species. The use of advanced technology and community-based approaches has proven to enhance compliance and conservation outcomes. In conclusion, to improve fisheries sustainability in conservation areas, it is necessary to increase resource allocation, strengthen anti-corruption mechanisms, and adopt technology and community-based strategies.